Chemotherapy, clocks, and the awareness of death: a quantitative phenomenological study - Moskalewicz, Marcin; Kordel, Piotr; Wiertlewska-Bielarz, Jadwiga (Frontiers in psychology, 2023)
Following a previous phenomenological study of lived time in ovarian cancer, this research aims to find how the frequency of chemotherapy affects orientation in time (the so-called “chemo-clock”) and the awareness of mortality of service users with various cancers. For this purpose, a variation of a front-loaded phenomenological method that combines scientific hypothesis testing with phenomenological insights of both conceptual and qualitative nature was developed. The study is based on a purposive quota sample of 440 participants representative of the Polish cancer population in terms of sex (m:f ratio 1:1) and age (m > 65 = 61%; f > 65 = 53%) and undergoing chemotherapy for at least a month. The exposure environmental factors of interest are temporal: the frequency of chemotherapy [weekly (N = 150), biweekly (N = 146), and triweekly (N = 144)] and time since the beginning of treatment. The study confirms the relevance of the “chemo-clock”—participants use the pace of hospital appointments for orientation in time, and significantly more often when in triweekly treatments (weekly 38%; biweekly 61%; triweekly 69.4%; V = 0.242, p < 0.001, while neither age nor time since the beginning of treatment differentiate the usage of calendar categories and the “chemo-clock”). Simultaneously, chemotherapy increases their awareness of finitude, which again correlates neither with age nor time since the beginning of treatment but is significantly stronger in those with lower chemotherapy frequencies. Lower treatment frequencies are thus associated with its increased significance in terms of its impact on how people with cancer measure time and whether they increasingly consider their mortality.
Gesehen am 26.05.2023